Applicability of the ultra-high radio frequency band (UHF) for hydrometeor detection by phase difference method - FABO, Peter; NEJEDLÍK, Pavol; KUBA, Michal; ONDERKA, Milan; PODHORSKÝ, Dušan (Contributions to Geophysics and Geodesy, 2021)
Hydrometeors (rain, fog and ice crystals) affect the transmission of electromagnetic signals. Previous research showed that alterations in the signal (amplitude and phase) are affected by the composition of the atmosphere, e.g. the presence of hydrometeors. The majority of hydrometeorological detecting methods are based on the attenuation of electromagnetic signals as they penetrate the atmosphere. Novel methods based on monitoring of parameters of the signal appeared in recent time. This article presents the first results from our investigation of how hydrometeors affect the phase differences in signals transmitted by BTS stations. Cell phone operators transmit electromagnetic signals in the 1 GHz frequency band. This paper describes a novel concept of how phase differences between two signals arriving at two different antennas can be used to detect hydrometeors. Although the described concept is assumed to be independent from the signal strength, the analysed signal must be detectable. The primary advantage of the proposed passive method is that the signal is almost ubiquitous and does not require demodulation. In densely populated areas, the network of BTS stations reaches a spatial density of 1 station per 1 km2 which gives excellent opportunity to use the signal for detection purposes.